2019
DOI: 10.1186/s40478-019-0785-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Nodal inhibits metastatic progression in retinoblastoma

Abstract: Retinoblastoma is the most common intraocular malignancy in children. We previously found that the ACVR1C/SMAD2 pathway is significantly upregulated in invasive retinoblastoma samples from patients. Here we studied the role of an ACVR1C ligand, Nodal, in regulating growth and metastatic dissemination in retinoblastoma. Inhibition of Nodal using multiple short hairpin (shRNAs) in WERI Rb1 and Y79 retinoblastoma cell cultures reduced growth by more than 90%, as determined by CCK-8 growth assay. Proliferation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In 2019, Asnaghi et al published two articles [ 26 , 27 ], in which they analyzed the function of ACVR1C/ALK7, a type I receptor of the TGF-ß family and its ligands Nodal, Activin A/B and GDF3. They found a three-fold increase of the receptor ACVR1C in invasive retinoblastomas, which invaded the optic nerve compared to non-invasive tumors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Asnaghi et al published two articles [ 26 , 27 ], in which they analyzed the function of ACVR1C/ALK7, a type I receptor of the TGF-ß family and its ligands Nodal, Activin A/B and GDF3. They found a three-fold increase of the receptor ACVR1C in invasive retinoblastomas, which invaded the optic nerve compared to non-invasive tumors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of Nodal also showed a reduction in the epithelial-to-mesenchymal transition (EMT) markers ZEB1 and snail and a reduction in migration of cells in the transwell invasion assay. Further, they showed a 34% reduction in the so- called minimum bonding sphere (MBS) at 4 dpi, which represented the migration of Y79 cells injected in the zebrafish eye [ 27 ]. Both articles from Asnaghi et al analyzed the pathways that are involved in cell migration of Y79 and WERI-RB-1 cells and retinoblastoma tumors that migrate along the optic nerve in humans, but they do not show the migration route in the injected zebrafish either.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent studies, the authors injected retinoblastoma cells intravitreally and observed how the cancer cells were able to disseminate outside the eye, and how spread was reduced when fish were treated with different inhibitors to block transcriptional pathways, potentially related to the development of the disease. These results may have translational value, opening the door to the discovery of new therapies for retinoblastoma [ 138 , 139 ]. Additionally, a novel orthotopic xenograft model for conjunctival melanoma has been recently established by retro-orbital injection, to mimic primary tumor spread and to test the possible repurposing of the anti-tumor ruthenium-based photosensitizer TLD1433 for retinoblastoma [ 124 ].…”
Section: Microenvironmentmentioning
confidence: 99%
“…This form of cancer accounts for ∼3% of the pediatric cancer population. [ 1 ] Its progression is activated due to the mutation in the Rb gene, responsible for the transcription tumor suppressor Rb protein. [ 2 ] Rb tumors occur either as endophytic or exophytic tumors.…”
Section: Introductionmentioning
confidence: 99%